Contribution of processing trade activities to Malaysia’s domestic economy - Hamid, Nur Adilah (2016)
Transformation of the current international trade pattern has mislead the information on how much Malaysia export are really made in Malaysia. Increased international outsourcings have spurred trade in intermediate goods, which is termed as processing trade. Malaysia is one the countries that actively participating in the processing trade activities in the Asian region. While empirical evidences in other countries clearly indicate the unfavorable effects on local economies, empirical works to quantify the impact of increased processing trade in Malaysia are clearly lagged behind. The fact is that the conventional national accounts framework does not separate the processing trade activities in the calculation of gross domestic products (GDP). In this study, we further improve the GDP accounting by separating the manufacturing sectors according to domestic and processing trade sectors, and integrating them consistently in a socalled ‘dualistic’ input-output table. Results clearly show that the processing trade sectors do not only associated with higher foreign content but also have lower growth linkages to the domestic economy. From the overall processing exports, only 39.6% are benefited to the domestic value added while another 60.4% are attributed to foreign content. Based on the findings, we strongly suggest the government to review the current Free Industrial Zone policies by putting more emphasize on the domestic manufacturing sectors and finding new focused sectors for exports.